Employee engagement and improvement as important principles of TQM in public health institutes - Vrtodušić Hrgović, Ana-Marija (Array, 2020)
Quality assurance in public health presents one of the key factors in the quality of health service. Accordingly, there is increasing awareness of the need to integrate quality systems and their principles into the healthcare system. Their role is important in the context of quality assurance in accordance with patient requirements as well as in the process of improving the quality of health care service. They are essential for the successful implementation of a quality management system and refer to customer focus, leadership, engagement of people, process approach, improvement, evidence–based decision making, and relationship management. This paper presents the results of a study among Croatian Institutes of Public Health with regard to the level of implementation of quality principles related to employee engagement, improvement and internal customer focus. Analysis focused on the relationship between focus on internal customer (employees) and improvements as well as the employee engagement and improvement respectively. Results show there is a strong positive relationship between employee engagement and improvements, while between internal customer focus and improvement the relationship has not been verified. In the context of standardization of quality of public health services, the paper aims to expand theoretical knowledge about TQM principles, with the emphasis on the employee engagement, internal customer focus (employees) and process improvement. The results can serve as a basis for improving the existing practice of quality management system implementation in the public health sector, with emphasis on employees.